Exploring the relationship between childhood maltreatment and cognitive bias in Chinese adults with major depressive disorder - Jintao Xiong; Mengqi Xu; Shazia Rehman; Jin Liu; Yumeng Ju; Mi Wang; Jinrong Sun; Xiaowen Lu; Qiangli Dong; Liang Zhang; Ping Wan; Hua Guo; et al. (Humanities & Social Sciences Communications)
Abstract This study aims to explore how different forms and cumulative experiences of childhood maltreatment (CM) relate to cognitive biases. A total of 121 participants diagnosed with major depressive disorder (MDD) and 120 healthy controls (HC) were recruited for this cross-sectional study. CM and cognitive biases were assessed, respectively, utilizing the Childhood Trauma Questionnaire and the Cognitive Bias Questionnaire. The latter evaluates two distinct dimensions of cognitive biases: depression and distortion, according to which cognitive characteristics were categorized into four combinations: depressed-distorted (D-D), depressed-nondistorted (D-ND), nondepressed-distorted (ND-D), and nondepressed-nondistorted (ND-ND). The Childhood Maltreatment Count (CMC) was defined as the cumulative count of distinct CM types. The findings indicate the association between CM and cognitive bias among the participants. In the MDD cohort, a significant association was observed between higher physical neglect scores and diminished ND-ND scores (β = –0.297, p = 0.012). In the HC group, no comparable relationship was identified. Furthermore, CMC was significantly correlated with decreased ND-ND scores both in the MDD group (β = −0.273, p = 0.006) and the HC group (β = −0.234, p = 0.010). This study underscores the significance of investigating the repercussions of physical neglect in MDD patients. Moreover, increased childhood trauma counts may function as a predisposing factor for more pronounced cognitive bias, with potential implications for clinical interventions and future research in diverse cultural contexts.